Experimental studies on the biological effects of chronic low dose-rate radiation exposure in mice: overview of the studies at the Institute for Environmental Sciences. (2nd April 2018) - Braga-Tanaka, Ignacia; Tanaka, Satoshi; Kohda, Atsushi; Takai, Daisaku; Nakamura, Shingo; Ono, Tetsuya; Tanaka, Kimio; Komura, Jun-ichiro
Abstract: This review summarizes the results of experiments conducted in the Institute for Environmental Sciences for the past 21 years, focusing on the biological effects of long-term low dose-rate radiation exposure on mice. Mice were chronically exposed to gamma rays at dose-rates of 0.05, 1 or 20 mGy/day for 400 days to total doses of 20, 400 or 8000 mGy, respectively. The dose rate 0.05 mGy/day is comparable to the dose limit for radiation workers. The parameters examined were lifespan, neoplasm incidence, antineoplasm immunity, body weight, chromosome aberration(s), gene mutation(s), alterations in mRNA and protein levels and trans-generational effects. At 20 mGy/day, all biological endpoints were significantly altered except neoplasm incidence in the offspring of exposed males. Slight but statistically significant changes in lifespan, neoplasm incidences, chromosome abnormalities and gene expressions were observed at 1 mGy/day. Except for transient alterations in the mRNA levels of some genes and increased liver neoplasm incidence attributed to radiation exposure, the remaining biological endpoints were not influenced after exposure to 0.05 mGy/day. Results suggest that chronic low dose-rate exposure may induce small biological effects.